O souvenir como elemento de valorização da memória e do patrimônio cultural da Universidade Federal de Santa Maria - Spiazzi, Evani Terezinha Chiapinotto (2020)
This work aimed to review cultural heritage, heritage education and souvenirs, aiming to reflect the importance of recognizing, valuing and preserving the heritage of the Federal University of Santa Maria, in the municipality of Santa Maria, RS, Brazil. The modernist architecture of the buildings, the works of art present in the panels and sculptures, and also the history and memory of the founder, were considered. José Mariano da Rocha Filho, when he brought to Santa Maria the first public university in the interior of Brazil in 1960. In order to highlight different elements, present in the material heritage of the university, it was sought from the souvenir to present products with commercialization potential. The study is configured as qualitative, exploratory, systematized based on the following stages: state of the art of theses, dissertations and scientific articles produced in the last ten years, focusing on the cultural heritage of UFSM; bibliographic review of the topics relevant to research; on-the-spot surveys with a photographic record of the cultural assets at the headquarters campus and also of the artifacts sold by the responsible sector at the university; application of a qualitative/quantitative online questionnaire, using the Google Forms tool, an electronic form created and made available at an electronic address, sent from February 3rd to March 6th, 2020, with a sample of 375 participants who have/had some type of link with UFSM. In the analysis of the results, the importance of the souvenir was evidenced as a potential element regarding the social-cultural-educational-environmental-economic-touristic aspects related to the recognition and valorization of the university's heritage. As the final product of this dissertation, we chose to propose three models of souvenirs highlighted in the research results, as suggestions of souvenirs representative of the institution's architectural, artistic and cultural heritage.